Molecular Weights of DNA from Bacteriophages T5, T5st(0), BF23, and BF23st(4) - Lang, Dimitrij (1976)
The DNA molecular weights were determined by calibrated electron microscopy. The results (in units of 10(6)) are: for T5, 77.4 ± 2.4; T5st(0), 72.4 ± 1.9; BF23, 76.7 ± 2.3; and BF23st(4), 71.4 ± 1.7.